Walking and walkability: do built environment measures correspond with pedestrian activity? - Humberto, Mateus (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
After the emergence of the term “walkability” in the 1990’s, many metrics have been developed with the aim of evaluating the quality of the built environment for pedestrians. More recently, researchers have also sought an association of these metrics with pedestrian behavior: do better sidewalk conditions and their surroundings correspond with higher pedestrian activity? To study the association of the built environment with the share of pedestrian movements, two different indexes, one at the city level (macro) and one at the neighborhood level (micro), were proposed using georeferenced data from São Paulo (Brazil). Once the available built environment and transport-related data were incorporated in a linear regression model, the neighborhood-level index (micro) and the share of pedestrian movements presented a strong positive correlation (adjusted R² = 0.797). In addition to the contributions to the relationship of walkability scores with data from developing countries, the discussions presented in this paper intend to provide insights into the territorial disparities in pedestrian mobility, mainly those related to socio-spatial segregation.